The Influence of Social Media Promotion and Sharia Financial Literacy on the Interest in Saving at Sharia Banks - Yenny April Yanti; Novi Yanti Sandra Dewi; Nur’aini Nur’aini (Owner : Riset dan Jurnal Akuntansi, 2026)
Although numerous previous studies have examined the role of Islamic financial literacy and digital promotion in influencing saving behavior, most of these studies remain descriptive in nature and have not sufficiently elaborated the conceptual mechanisms underlying the formation of saving intentions within a behavioral theory framework, particularly among generations that grow up within a digital ecosystem. Addressing this gap, the present study aims to investigate the influence of Islamic financial literacy and social media promotion on the intention to save in Islamic banks, both partially and simultaneously, by positioning these variables as determinants of behavioral intention. This study employs a quantitative approach involving 101 respondents who are active social media users in the Province of West Nusa Tenggara and have the potential to become customers of Islamic banks. Data were analyzed using descriptive statistics and multiple linear regression analysis. The results indicate that Islamic financial literacy exerts a more dominant influence (? = 0.481; p < 0.001) compared to social media promotion (? = 0.325; p < 0.001), with a coefficient of determination (R²) of 0.548, suggesting that the two independent variables collectively explain 54.8% of the variance in saving intention.The mean values of variable X1 were 69.87, X2 were 69.86, and Y were 70.20, while the Shapiro–Wilk test results (p > 0.05) indicate that the data are normally distributed. Theoretically, these findings contribute to the development of a behavioral model of Islamic saving by highlighting Islamic financial literacy as a determinant of attitude formation and social media promotion as a social mechanism that strengthens saving intentions in the digital era. Thus, this study enriches the literature on Islamic financial behavior and provides strategic implications for strengthening educational initiatives and technology-based marketing strategies for Islamic banking institutions.